MERGER ANALYSIS ON GLOBAL AUTOMOTIVE INDUSTRY A CASE STUDY AT DAIMLER-CHRYSLER AUTOMOTIVE COMPANY - Nur Fitriani; Syamsu Alam; Muhammad Sobarsyah (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2021)
This research aims to analyze mergers in global automotive industries to find out the causes of merger failure in the global automotive industry. This research used a case study at Daimler-Chrysler automotive company. The decision to committed a merger strategy had an impact on the Daimler-Chrysler company, mainly in cultural differences between Germany and the United States of America, where the Daimler-Benz and Chrysler Corporation originated. This research used a literature study research method by using library research related to the Daimler-Chrysler merger, with qualitative descriptive analysis techniques. The results of this research indicated that the agreement to do a merger strategy between Daimler-Benz and Chrysler Corporation was caused by cultural differences as a new Daimler-Chrysler company. It makes Daimler-Chrysler must be able to collaborate and synergized with each other for merger integration can be successful. However, this was not able to be done by Daimler-Chrysler, so the merger between Daimler-Chrysler was failed in the end.